2003
DOI: 10.1016/s0195-668x(03)00112-x
|View full text |Cite
|
Sign up to set email alerts
|

Nurse-led heart failure clinics improve survival and self-care behaviour in patients with heart failureResults from a prospective, randomised trial

Abstract: Follow up after hospitalisation at a nurse-led heart failure clinic can improve survival and self-care behaviour in patients with heart failure as well as reduce the number of events, readmissions and days in hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
320
5
25

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 414 publications
(358 citation statements)
references
References 27 publications
8
320
5
25
Order By: Relevance
“…First, in our study, most participants saw one only caregiver, whereas in previous studies examining the role of nurses in heart failure clinics, the patient was always seen by various caregivers, including a cardiologist. [4][5][6] Second, our study group consisted of symptom-free relatives, whereas previous studies covered patients diagnosed with a cardiac or other disease. Finally, the setting of our study differed from that of previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…First, in our study, most participants saw one only caregiver, whereas in previous studies examining the role of nurses in heart failure clinics, the patient was always seen by various caregivers, including a cardiologist. [4][5][6] Second, our study group consisted of symptom-free relatives, whereas previous studies covered patients diagnosed with a cardiac or other disease. Finally, the setting of our study differed from that of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] A study in low risk patients who had had a recent myocardial infarction demonstrated that nurse practitioners can deliver a quality of care equal to or better than conventional specialist care. 4 Improved survival and self-care behaviour was seen in patients with heart failure when they were treated by specially educated and experienced cardiac nurses.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, nurses are the health professionals most closely involved, according to the meta‐review of 15 meta‐analyses by Savard et al 9 A considerable number of these meta‐analyses mentioned dose titration by HF nurses. In the clinical trials included, nurses titrated ACEIs, ARBs, BBs, K, diuretics, MRAs, and digoxin,10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21 assessed the dose reached,13, 14, 19, 20 and initiated treatment following a protocol 10, 12, 14, 15, 17. Hardly any similar research has been conducted in Spain.…”
Section: Introductionmentioning
confidence: 99%